Estratégias autorregulatórias no cenário de riscos dos resíduos nanotecnológicos a partir da economia circular: uma proposta de rastreabilidade dos nanomateriais - Leal, Daniele Weber da Silva (Universidade do Vale do Rio dos Sinos, 2023)
This thesis intends to demonstrate the impacts of the Nanotechnological Revolution in contemporary society, situated in the scenario of the Fourth Industrial Revolution. Analyze the complexities of this technology, ranging from the same characteristics that make nanomaterials different and beneficial, while also generating concerns and doubts about the risk, about their behavior, especially regarding their interaction with the ecosystem. The focus of this study is on nanotechnological waste, or nanowaste, with emphasis on nanoplastics, which are part of a situation of risk and the need to adopt sustainable development and a safer final destination. It is intended to encourage empirical research with a proposal for a systematic review of the literature, especially in the CAPES Periodicals Portal, based on search keywords, with subsequent analysis of the extracted data, envisioning the pertinence of the research in the scientific community. The problem of this Doctoral Thesis presents the following structuring contours about the absence of specific regulations for nanotechnological waste, and how the adoption of the Circular Economy by companies, founded on (nano)sustainability, can implement the implementation of traceability of nanoproducts (from cradle to the cradle), and of nanotechnological waste, which, consequently, will effect risk management and selfregulation, in a space illuminated by the sustainability required in this scenario permeated by nanotechnological uncertainties and risks, in respect of the greater objective of SDGs 9 and 12 of the United Nations (UN). In addition, it seeks to build the structuring elements for the necessary (self)regulation based on Teubner's Constitutional Fragments, which identifies new actors and unprecedented spaces of self-regulation, through the adoption of sustainable measures imposed in this scenario of “nanotechnological risks”, presenting as a possible alternative, a project for “traceability of nanotechnological waste” – based on the very basic principles of the Circular Economy – in parallel with the Bill pending in the Chamber of Deputies nº 7.088, of 2017, by Rômulo Gouveia, which amends Law nº 12,305, of 2010, which establishes the National Solid Waste Policy, to provide for the tracking of hazardous waste. The general objective of the thesis is to study a self-regulatory alternative in the face of a specific absence for nanoproducts and nanotechnological residues. To this end, it will be analyzed how the adoption of the Circular Economy by companies, founded on (nano)sustainability, can implement the traceability of nanoproducts and nanotechnological residues, also carrying out the specific focus on nanoplastics as a new attention within of waste. The self-regulatory basis will be explored through instruments with regulatory potential in the European Union, with a focus on the OECD. The investigation will be carried out using the systemic-constructivist methodology, with functional analysis (LUHMANN). As final considerations, the feasibility of adopting the circular economy based on (nano)sustainability is presented, as well as the possibility of implementing traceability of nanomaterials through self-regulatory structures.
Keywords: Nanotecnologias; Nanowaste; Nanoplástico; Economia circular; Rastreabilidade; Gestão de risco nanotecnológico; Autorregulação; Fragmentos Constitucionais de Teubner; Nanotechnologies; Nanoplastic; Circular economy; Traceability; Nanotechnology risk management; Self-regulation; Teubner's Constitutional Fragments; ACCNPQ::Ciências Sociais Aplicadas::Direito